The Pericapsular Nerve Group (PENG) block combined with Local Infiltration Analgesia (LIA) compared to placebo and LIA in hip arthroplasty surgery a multi-center double-blinded randomized-controlled trial - D.-Yin, Lin (Springer, 2023)
CC BY